Prevention of Corruption Act, 1988 - Khetrapal, B. S.; Khetrapal, Puja (Indore Puja Law House, 2020)
An Act to consolidate and amend the law relating to the prevention of corruption and for matters connected therewith. follows: Be it enacted by Parliament in the Thirty-ninth Year of the Republic of India
Keywords: Prevention of Corruption